Effects of aerobic exercise on body composition and exerkines in colorectal cancer survivors - Eunhan Cho; Miranda Chodzko; Stephanie L. E. Compton; Shengping Yang; Steven Heymsfield; Guillaume Spielmann; Guillaume Spielmann; Justin C. Brown; Justin C. Brown; Justin C. Brown; Justin C. Brown; Justin C. Brown (Frontiers in Sports and Active Living)
IntroductionPhysical activity improves immune competency and is associated with a lower rate of cancer recurrence in colorectal cancer survivors. However, the exact mechanisms underlying these improvements remain unclear. Exercise-derived cytokines (exerkines), particularly IL-7 and IL-15, are crucial in maintaining optimal immune health. This study investigated whether a 12-week structured exercise training intervention increases IL-7 and IL-15 in colorectal cancer survivors.MethodsSixty colorectal cancer survivors were randomized to a moderate-intensity home-based aerobic exercise group (150 min/week) or a control group for 12 weeks. IL-7 and IL-15 were quantified using ELISA, and body composition was measured using dual-energy x-ray absorptiometry.ResultsAt baseline, participants treated with chemotherapy had lower IL-7 than those not treated with chemotherapy [−3.3 pg/ml (95% CI: −1.3, −5.4); p = 0.002]. Baseline fitness capacity correlated with IL-15 (r = −0.37; p = 0.004). IL-7 increased in the exercise group [2.3 pg/ml (95% CI: 0.9, 3.8; p = 0.003)], but not in the control group [1.2 pg/ml (95% CI: 0.3, 2.8; p = 0.31)]. IL-15 did not differ between groups. Longitudinal changes in IL-15 were associated with changes in body composition.DiscussionAerobic exercise may improve immune function in colorectal cancer survivors by restoring IL-7 after chemotherapy and improving IL-15 by altering body composition. Clinical Trial Registration[https://clinicaltrials.gov/study/NCT03975491], identifier [NCT03975491].